The Using of Peer Tutoring Strategies in Improving Students’ Achievement and Involvement in Learning Mathematics - Titin Hartini (Acitya: Journal of Teaching and Education, 2019)
Most students encountered a problem in understanding Mathematics and were not actively involved in learning activities. A method or learning strategies would be assigned to help the students master the concept of mathematics.The aim of this study was to find out wether the use of Peer Tutoring strategies in the classroom could increase students’ achievement and involvement in learning Mathematics.. The subjects of this study were the second grade students of SMAN 10 Samarinda. The approach of this study was an action reasearh, applying three syclus. The indicator of success was that 80 % of students could reach minimum grade (70). In each syclus, there were planning, apllying, observing, and reflexing. Post-tests in each syclus were used as instrument of students’ achievement data. The result showed that there was an increase between the first syclus post-test (60 %), the second syclus post-test (73 %), and the third syclus post-test (90 %). Besides that, the students got involved better in peer tutoring activity of respectively syclus. This indicates that Peer tutoring strategies incresed students’ achievement and involvement in learning Mathematics. This suggests that Peer Tutoring strategies can be used as an alternative strategy in teaching Mathematics.